Language ideologies in science education. Issue 4 (12th March 2019) - Lemmi, Catherine; Brown, Bryan A.; Wild, Andrew; Zummo, Lynne; Sedlacek, Quentin
Abstract: Drawing on sociolinguistics research regarding common beliefs and justifications about language, we applied notions of language ideology to an analysis of the formative assessment practices of secondary science teachers from linguistically diverse schools. We identified two language ideologies that were demonstrated by teachers as they engaged in the formative assessment of student work. Here, we introduce the terms language‐exclusive ideology and language‐inclusive ideology . A language‐exclusive ideology holds that certain forms of language are expected in a science class, and others are not appropriate. What we have termed a language‐inclusive ideology suggests that multiple forms of language use are acceptable in science classrooms, and this approach finds synergies with the literature on translanguaging, or the integration of multiple languages for complex communicative purposes. We argue that science teacher educators should consider teachers' language ideologies as they prepare professional development and preservice teacher education curriculum materials, and we discuss potential implications for science education and teacher education. Finally, we call for more explicit consideration of issues of language ideology within the science education community to understand how various approaches to language can provide affordances or barriers to content learning and language development.